2014
DOI: 10.1186/s13073-014-0076-4
|View full text |Cite
|
Sign up to set email alerts
|

A large scale expression study associates uc.283-plus lncRNA with pluripotent stem cells and human glioma

Abstract: BackgroundThere are 481 ultra-conserved regions (UCRs) longer than 200 bases in the genomes of human, mouse and rat. These DNA sequences are absolutely conserved and show 100% identity with no insertions or deletions. About half of these UCRs are reported as transcribed and many correspond to long non-coding RNAs (lncRNAs).MethodsWe used custom microarrays with 962 probes representing sense and antisense sequences for the 481 UCRs to examine their expression across 374 normal samples from 46 different tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 42 publications
0
28
0
2
Order By: Relevance
“…The main molecular mechanism of T-UCE activity described to date is its ‘decoy’ function. By acting as natural sponges, these lncRNAs can sequester miRNAs via sequence complementarity [ 107 110 ]. Decoy binding sites within T-UCEs also act through chromatin remodeling by interplaying with distinct regulatory molecules including epigenetic modifiers, transcription factors, and catalytic proteins [ 111 , 112 ].…”
Section: Transcribed Ucesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main molecular mechanism of T-UCE activity described to date is its ‘decoy’ function. By acting as natural sponges, these lncRNAs can sequester miRNAs via sequence complementarity [ 107 110 ]. Decoy binding sites within T-UCEs also act through chromatin remodeling by interplaying with distinct regulatory molecules including epigenetic modifiers, transcription factors, and catalytic proteins [ 111 , 112 ].…”
Section: Transcribed Ucesmentioning
confidence: 99%
“…More recent large-scale efforts, employing genome-wide sequencing of multiple tissues, identified T-UC.283+ as the T-UCE most expressed in ESCs, iPSCs and in several embryonic and extra-embryonic tissues. Although no specific function of T-UC283+ has been elucidated, it has been suggested that it may be involved in pluripotency maintenance but also during the first-cell lineage specification [ 107 ].…”
Section: Transcribed Ucesmentioning
confidence: 99%
“…The noncoding panorama is a real opportunity to reveal new biomarkers or potential targets: in this landscape long noncoding RNAs (lncRNAs) are an emerging class of key regulatory RNAs that do not code for protein and are not translated [5]. lncRNAs are crucial players in various key biological processes that include dosage compensation, genomic imprinting, chromatin organization, gene regulation, and alternative splicing [6]. lncRNA mechanism of action need still to be widely revealed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Another similar finding was the association of methylated Uc283 with the improvement of clinical outcome. Recently, Galasso et al showed that Uc283 is highly expressed in pluripotent embryonic stem cells (ESCs) inducing pluripotency while it is overexpressed in gliomas and prostate cancer and less expressed in CRC [28]. In addition, a group led by Dr Esteller showed that Uc283 binds to pri-miRNA-195, leading to downregulation of mature miRNA-195 [29], a miRNA that is known to suppress metastasis and proliferation of CRC [30].…”
Section: Discussionmentioning
confidence: 99%